GENDER DISPARITIES IN STUDENT SUPPORT SERVICES: A COMPARATIVE STUDY OF HIGHER EDUCATION INSTITUTIONS IN ZIMBABWE AND ESWATINI (NAU Journal of Technology and Vocational Education, 2026)
Gender disparities in student support services pose a significant barrier to equitable academic outcomes in African higher education institutions. While existing scholarship has examined gender gaps in student recruitment, programme participation and academic performance, disparities in institutional support systems have received comparatively less attention despite evidence that support services critically shape student retention and achievement. This study explored gender-based disparities in student support services at five higher education institutions, three in Zimbabwe and two in Eswatini. Employing a descriptive survey design, data were collected from 250 students (50 per institution) through open-ended questionnaires and unstructured interviews. Data were analysed using thematic analysis. The findings of this study indicate that gender disparities are visible in most student support systems, with female students disproportionately disadvantaged across financial aid, career services, counselling and residential facilities. These findings are consistent with broader scholarship on gender inequality in African higher education, which identifies patriarchal institutional cultures, inadequate gender-sensitive policies, and resource disparities as persistent structural barriers to equitable student support The study concludes that gender-sensitive institutional policies, targeted financial support mechanisms, and inclusive frameworks for service delivery are essential to bridging these disparities and advancing equitable higher education in both countries.
Keywords: gender equity; student affairs; higher education; Zimbabwe; Eswatini; academic support services; gender-based disparities